E-HATS: A symmetric key encryption algorithm with dynamic substitution rule - Mullick, Vikalp (2014 9th International Conference on Industrial and Information Systems (ICIIS), 2014)
E-HATS is a symmetric key encryption algorithm which encrypts and decrypts a 128-bit data block. E-HATS inherits the simplicity, feistel nature of DES and security analogous to AES. Key Updation is addressed by 16 additional bits in the cipher key. A Dynamic Substitution Rule is used in the substitution step. At the software level, E-HATS exhibits superior avalanche characteristics, achieves a reduction of 7.2% in average encryption time per block and a gain of 10.35% in throughput compared to AES. E-HATS implemented on Artix 7 FPGA platform achieves 79%, 58.24% reduction in hardware and power requirements, respectively compared to AES. E-HATS is not vulnerable to differential and linear cryptanalysis and a brute force attack is 16 P 4 times laborious than AES.